A content analysis of Non-Stereotypical Gender Representations (NSGR) in Philippine TV advertisements of stereotypically gendered products - Quima, Nikkah Shayne L. (2023)
The NSGR advertisements are rapidly expanding throughout Asia. In some advertisements for products that are typically associated with one gender or the other, such as those for cooking, child care, alcoholic beverages, and food, both men and women have been spotted. The researcher's primary focus will be on analyzing the content of three television advertisements for stereotypically gendered products that fall into each of the previously specified categories. In the cooking category, the researcher will examine advertisements for Knorr seasonings, Nestle All-Purpose Cream, and Maggi Magic Sarap; in the childcare category, EQ Diaper, Nido, and Baby Dove products; in the alcoholic beverage category, GSM Blue Mojito, San Miguel Flavored Beer, and Emperador; and in the food category, Lucky Me! Pancit Canton, Selecta Cornetto Ice Cream, and Century Tuna from 2018?2021 that were available on YouTube. A total of 182 advertisements were collected and examined using qualitative analysis with a coding method adapted from Furnham and Li?s (2008) study on ?Gender portrayal in food and beverage advertisements in Hong Kong: a content analytic study? to identify how are stereotypically gendered products promoted, and examine the presence and non-presence of NSGR in Philippine TV advertisements. The advertisements were coded and categorized based on the central figure, age group, mode of presentation, credibility basis, role, location, argument, reward type, background, and end comment. The finding of the study shows that men and women were still portrayed stereotypically in the advertisements of stereotypically gendered products. Women still dominate the advertisements for cooking and childcare products, while men still dominate the advertisements for alcoholic beverages and food products. The non-stereotypical gender representation (NSGR) phenomenon in advertising made it possible for genders to be featured in advertisements for items that are typically sold or traditionally advertised to or with the opposite gender. Although there are NSGR traits present in some of the advertisements collected, they were very limited.